Implementation of PSAK 73: Study of Financial Ratios of PT Aneka Tambang, Tbk - Heni Suryanti (International Journal of Social Service and Research, 2023)
This research aims to analyze changes in PSAK regarding rent, which affects financial performance at PT Aneka Tambang Tbk. Implementing PSAK 73 requires lessees to classify operating leases into finance leases except for short-term leases and assets with a low basis. Lessees with future operating lease commitments must capitalize the lease assets and liabilities. Lease capitalization causes assets and liabilities to increase and equity to decrease in the statement of financial position while net profit in the comprehensive income statement increases. This is because the expenses that arise from the capitalization of rent, namely depreciation and interest expenses, are smaller than the rent expenses written off. The quantitative descriptive research uses secondary data sources in the form of PT Aneka Tambang Tbk's financial reports in 2019 before changes to the PSAK Lease and in 2020 after changes to PSAK. The research results show that changes to PSAK impact the company's financial performance as assessed by financial ratios.